Simple Computer Vision Algorithm Production using OpenCV for “Virtual Ecosystem” project. - Andrew Willis; Kemal Hasan (IJNMT (International Journal of New Media Technology), 2020)
The main purposes of this research is to produce aComputer Vision (CV) algorithm using various library in pythonprogramming language (mainly OpenCV, Numpy, and ZBar) toautomate extraction and process information from an analogdrawing into a digital image to be used in the “Virtual Ecosystem”project. The Computer Vision step will include detecting datawithin the analog drawing using QR-code, determine drawingarea, replace white background with certain threshold withtransparency, and finally save the digital image following requiredratio.